Beyond Screen Time: How Technology is Building the Preschool Brain - Sayed Mahbub Hasan Amiri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2026)
The discussion surrounding early childhood technology continues to concentrate predominantly on the duration of screen time, overlooking a critical examination of how particular digital tools qualitatively affect cognitive development. This study asked 74 early childhood teachers and administrators from different types of schools (public, private, Montessori, Reggio, and Head Start) about how they use technology with kids ages 3 to 5 and what effects it has on their thinking. Data indicates a transition from passive consumption to active creation. The study strongly links tablet-based creation apps and digital cameras to the observed 31% increase in creativity and self-expression. There is a strong correlation between educational robotics and coding kits and the growth of problem-solving and critical thinking skills 28%. Interactive e-books and audio resources help people learn languages 22%, especially if they speak more than one language. Success is not determined by duration but by purposeful integration that employs technology as a medium for documentation, collaboration, and targeted skill development within play-based teaching. It is important to move beyond the